Transforming workplace relations in New Zealand: a retrospective. (2nd January 2018) - Barry, Michael
ABSTRACT: This article analyses the transformation of New Zealand employment relations through an examination of a volume produced to mark the 40th Anniversary of the first publication of the New Zealand Journal of Industrial Relations. The book explores a fundamental shift away from state intervention that promoted pluralist participation in industrial relations towards a legal model based on the assertion of managerial prerogative and the principles of the common law. The aim of this article was to review the volume, highlighting both its strengths and weaknesses in exploring the last 40 years of New Zealand employment relations. The article also reflects on the New Zealand transformation in the light of international experience, particularly that of Australia.